Fabrication and Characterization of Starch-Based Biodegradable Polymer with Polyvinyl Alcohol - Pokhrel, Shanta; Rai, Lalita Sundari (Journal of Nepal Chemical Society, 2019)
Starch is a renewable, biodegradable and low-cost natural biopolymer with high availability. Starch was extracted from Solanum tuberosum (potatoes) and its preliminary properties were studied. The structure of extracted starch was characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). A series of starch-based biodegradable blends, with polyvinyl alcohol (PVA) were prepared by using glycerol as a plasticizer and citric acid as a cross-linking agent, through solution casting method and their biodegradable properties were studied. The structure of the blend was characterized by Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimeter (DSC). The morphology of starch shows the potato starch has oval or ellipsoid in the structure having a size of 20-35 µm. The compatibility of the two components can be improved by the hydroxyl group present on both starch and PVA. As compared to pure polyvinyl, the melting point of the blend was decreased. The blends were found degradable within a weak.